Prevalence of female genital cutting among Egyptian girls - Mohammed A Tag-Eldin; Mohsen A Gadallah; Mahmoud N Al-Tayeb; Mostafa Abdel-Aty; Esmat Mansour; Mona Sallem
OBJECTIVE: Female genital cutting (FGC) is the collective name given to traditional practices that involve partial or total cutting away of the female external genitalia whether for cultural or other non-therapeutic reasons. In Egypt, the result of the Demographic Health Survey in 2000 revealed that 97% of married women included in the survey experienced FGC. The aim of this study is to measure the prevalence of FGC among schoolgirls in Egypt. METHODS: Multistage random technique was applied for site selection. First, Egypt was divided into five geographical areas; Greater Cairo, Lower Egypt, Upper Egypt, Sinai and Suez Canal Region. Second, from each governorate, two educational districts were selected randomly (except Luxor). In each of the selected districts, the schools were divided into primary, preparatory and secondary schools. In each education stage, the schools were divided into rural, urban, government and private. The total number of females interviewed was 38 816. FINDINGS: The prevalence of FGC among schoolgirls in Egypt was 50.3%. The prevalence of FGC was 46.2% in government urban schools, 9.2% in private urban schools and 61.7% in rural schools. Educational levels of mother and father were negatively associated with FGC (P < 0.001). The mean age of the time of FGC was 10.1 ± 2.3 years. CONCLUSION: FGC prevalence is lowering, yet more active education at the grass-roots level is needed to create change.